1993
DOI: 10.1021/bi00070a031
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and kinetic studies of imine product formation in the oxidation of p-(N,N-dimethylamino)benzylamine analogs by monoamine oxidase B

Abstract: The oxidative deamination of p-(N,N-dimethylamino)benzylamine and N-methyl-p-(N,N-dimethylamino)benzylamine by bovine liver monoamine oxidase B has been investigated by absorption spectral, steady-state, and stopped-flow kinetic studies. An absorbing intermediate with a maximum at 390 nm is observed with either analogue in turnover experiments at neutral pH and is identified as due to the formation of protonated imine as the initial product. p-(N,N-Dimethylamino)benzaldehyde is the final product formed from ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…This, however, does not rule out the possibility that, when it is finally liberated from the enzyme, the imine formed could be protonated, because, during its departure, changes in the environment could make the protonation feasible. This would then fully agree with Edmondson et al,44 who performed spectral and stop‐flow kinetic measurements on the bovine MAO–B oxidation of p ‐(dimethylamino)benzylamines and showed that the protonated imine is the form that is released from the enzyme. Also, the fact that the flavin cofactor is fully reduced to FADH 2 enables an important prerequisite for MAO regeneration by molecular oxygen to revert flavin into its oxidized form (FAD) by creating hydrogen peroxide (H 2 O 2 ), a reaction for which two hydrogen atoms are required.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This, however, does not rule out the possibility that, when it is finally liberated from the enzyme, the imine formed could be protonated, because, during its departure, changes in the environment could make the protonation feasible. This would then fully agree with Edmondson et al,44 who performed spectral and stop‐flow kinetic measurements on the bovine MAO–B oxidation of p ‐(dimethylamino)benzylamines and showed that the protonated imine is the form that is released from the enzyme. Also, the fact that the flavin cofactor is fully reduced to FADH 2 enables an important prerequisite for MAO regeneration by molecular oxygen to revert flavin into its oxidized form (FAD) by creating hydrogen peroxide (H 2 O 2 ), a reaction for which two hydrogen atoms are required.…”
Section: Resultssupporting
confidence: 88%
“…First, it would be difficult for a protonated imine to leave the active site, because on its way out it would strongly bind to the “aromatic cage” through favourable cation–π interactions 34. Secondly, it is well established that the final imine hydrolysis to aldehydes occurs non‐enzymatically outside the MAO 44,45. However, the protonated product would immediately be hydrolysed by the nearest water molecule within the enzyme, because in organic chemistry this reaction readily proceeds with the protonated imine under acidic conditions 37…”
Section: Resultsmentioning
confidence: 99%
“…Monoamine oxidases A and B (MAO A and MAO B) are outer mitochondrial membrane proteins that catalyze the oxidation of primary, secondary, and tertiary amines, including several neurotransmitters, to the corresponding imines; the oxidized products are hydrolyzed nonenzymatically to the respective aldehydes or ketones (8) (Scheme 3). The two enzymes share 70% amino acid identity, and both contain a covalently-bound FAD cofactor attached to an enzyme cysteine via the 8α-methylene of the isoalloxazine ring (9).…”
Section: Monoamine Oxidases a And Bmentioning
confidence: 99%
“…For most substrates both MAO A and MAO B follow the lower loop of the pathway shown in Scheme 1 in which oxygen reacts with the enzyme-product complex before product has dissociated. There is general consensus that the deprotonated (rather than the protonated) amine moiety on the substrate binds to the active site on the enzymes and is oxidized to the protonated imine (4) (found with both MAO B and MAO A) with the covalent 8α-S-cysteinyl FAD cofactor being reduced to its hydroquinone form. To complete the catalytic cycle, the reduced FAD cofactor reacts with O 2 to generate oxidized flavin and H 2 O 2 .…”
mentioning
confidence: 99%